Effect of Structural Stiffness on the Stability of Pulsatile Poiseuille Flow Through a Compliant Channel - Tsigklifis, Konstantinos; Lucey, A. (Springer, 2018)
This book presents the proceedings of the Symposium on Fluid-Structure-Sound Interactions and Control (FSSIC), (held in Tokyo on Aug. 21-24, 2017), which largely focused on advances in the theory, experiments on, and numerical simulation of ...